2011
DOI: 10.1159/000327377
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Dermatosis Shortly after Implantation Associated with Parental Class II HLA Compatibility and Maternal Immune Activation: Preliminary Report of a Prospective Case Series

Abstract: Background: Pregnancy represents a semiallograft, subject to similar immune responses as allogeneic organ transplants. Tolerance of pregnancy appears best with maximal class II HLA heterogeneity between mother and father, while compatibilities are associated with increased pregnancy loss and maternal autoimmunity. Tolerance abnormalities often involve skin reactions. Abnormalities in tolerance of the fetal graft may do the same. Objective: To define the characteristics of a newly described dermatosis in very e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Like Gleicher has pointed out in a number of publications, these unexplained conditions of pregnancy exhibit characteristics similar to immunological conditions observed in organ transplant rejection [28] and/or graft versus host disease (GVHD) [29], therefore ICP may represent the complications of normal tolerance of the fetal semi-allograft by the maternal immune system [30]. Herein, our microarray results revealed that genes associated with immune response, CXCL6 , CXCL14 and IL-7R were up-regulated in mild ICP and further up-regulated in severe ICP, while CCL3 and CCL25 were only up-regulated in severe ICP, which suggest that abnormal immune response in patients’ placentas might be positively correlated to the severity of ICP.…”
Section: Resultsmentioning
confidence: 99%
“…Like Gleicher has pointed out in a number of publications, these unexplained conditions of pregnancy exhibit characteristics similar to immunological conditions observed in organ transplant rejection [28] and/or graft versus host disease (GVHD) [29], therefore ICP may represent the complications of normal tolerance of the fetal semi-allograft by the maternal immune system [30]. Herein, our microarray results revealed that genes associated with immune response, CXCL6 , CXCL14 and IL-7R were up-regulated in mild ICP and further up-regulated in severe ICP, while CCL3 and CCL25 were only up-regulated in severe ICP, which suggest that abnormal immune response in patients’ placentas might be positively correlated to the severity of ICP.…”
Section: Resultsmentioning
confidence: 99%
“…19 Likewise, Gleicher and Barad suggested that dermatosis of pregnancy including ICP may represent similar characteristics observed in allogenic graft rejection. 31 The ADAMTS-12 is already known to be required in allergic and normal inflammation, as ADAMTS-12-deficient mice exhibited more severe inflammation accompanied by neutrophilia in affected tissues. 20,32,33 The results of our study are in consistence with the above-mentioned reports, as we found significantly decreased levels of ADAMTS-12 in ICP placentas.…”
Section: Discussionmentioning
confidence: 99%